Drivers and disruptors shaping the future of agriculture and the food system in LAC: Climate change and trade tensions - Piñeiro, Valeria; Thomas, Timothy S.; Laborde Debucquet, David; Díaz-Bonilla, Eugenio (International Food Policy Research Institute, 2020)
Agri-food production remains vital to the economies in Latin America and the Caribbean (LAC). Food systems are rapidly changing and are driven by income growth, (urban) population growth, shifts in dietary preferences, and agricultural productivity growth. Food systems are also under threat from disrupters like climate change and distorting policies (including trade wars). This paper makes two quantitative, forward-looking assessments for the future of food and agriculture in the LAC region. The first focuses on the long-term prospects - given projected pathways for the main drivers and under the threat of climate change. The second focuses on current vulnerability of LACs agri-food system to short-term disrupters with special reference to impacts of global trade wars and the prospects for reducing that vulnerability. The implications are not uniform across the countries in the region, but vary greatly depending on economic and demographic size, contribution of the agricultural sector to national GDP, natural resource endowments, ecological and climatic characteristics, level of sophistication of rural and agrarian institutions, available technology, farm-size distribution and tenure systems. Policy interventions to address the challenges will need to consider those differences in initial conditions. The foresight assessments are built on IFPRI’s core global model frameworks, IMPACT and MIRAGRODEP. They allow to capture the complexity of agri-food system development and the scenario analysis helps quantify the relative importance of the drivers and disruptors of food system change, which in turn should be of essential to policymakers in setting priorities for steering towards sustainable and stable food systems capable of meeting twenty-first century challenges.